If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k in (-oo:+oo)
6*k+3 = 23-(4*k) // - 23-(4*k)
6*k+4*k-23+3 = 0
10*k-20 = 0 // + 20
10*k = 20 // : 10
k = 20/10
k = 2
k = 2
| 4a+5=-39-7a | | -7d-2=4d+75 | | 8-5w=5w-32 | | -2d+2=-7d-13 | | 1+6d=d+1 | | 3a+3=-2a-12 | | 4t+7=5+5t | | 6k-6=3k+3 | | 4a+10=7a-2 | | 5-4k=5k+50 | | -4t+2=112+6t | | -2+t=2t-1 | | 5x+2=2x+26 | | -8+2m=-2m+12 | | x+4=6x+4 | | 7+6k=-7k+7 | | 2m+2=-7m+56 | | 3a+3=-5a-37 | | 10-4t=-3t+1 | | 2b-1=-b+29 | | 2w-3=-12+5w | | 9+x=5x-19 | | 10-7k=3k+10 | | -2t+2=7t-16 | | (3/8)/100 | | 6n-7=5n-3 | | -7+7a=-4a-106 | | -3m+2=m-2 | | 3/8/100 | | -8-7t=-4t-44 | | 5-n=2n+17 | | 10+7n=6n+14 |